2022
DOI: 10.1038/s41598-022-22100-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to particulate matter was associated with increased dementia risk using both traditional approaches and novel machine learning methods

Abstract: Air pollution exposure has been linked to various diseases, including dementia. However, a novel method for investigating the associations between air pollution exposure and disease is lacking. The objective of this study was to investigate whether long-term exposure to ambient particulate air pollution increases dementia risk using both the traditional Cox model approach and a novel machine learning (ML) with random forest (RF) method. We used health data from a national population-based cohort in Taiwan from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
2
0
0
Order By: Relevance
“…The current study revealed significant associations between exposure to PM2.5 and the incidence of dementia in patients with stroke, even after adjusting for age, gender, and various comorbidities. These results are consistent with previous research which has revealed that exposure to particulate air pollution, particularly PM2.5, increases the risk of developing dementia ( Smargiassi et al, 2020 ; Yan et al, 2022 ; Abolhasani et al, 2023 ). A large national population-based cohort study conducted in Taiwan revealed that an increase in the PM2.5 concentration by one IQR (10.29) elevated the risk of dementia by approximately 5% (HR = 1.05, 95% CI = 1.04–1.05) ( Yan et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study revealed significant associations between exposure to PM2.5 and the incidence of dementia in patients with stroke, even after adjusting for age, gender, and various comorbidities. These results are consistent with previous research which has revealed that exposure to particulate air pollution, particularly PM2.5, increases the risk of developing dementia ( Smargiassi et al, 2020 ; Yan et al, 2022 ; Abolhasani et al, 2023 ). A large national population-based cohort study conducted in Taiwan revealed that an increase in the PM2.5 concentration by one IQR (10.29) elevated the risk of dementia by approximately 5% (HR = 1.05, 95% CI = 1.04–1.05) ( Yan et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with previous research which has revealed that exposure to particulate air pollution, particularly PM2.5, increases the risk of developing dementia ( Smargiassi et al, 2020 ; Yan et al, 2022 ; Abolhasani et al, 2023 ). A large national population-based cohort study conducted in Taiwan revealed that an increase in the PM2.5 concentration by one IQR (10.29) elevated the risk of dementia by approximately 5% (HR = 1.05, 95% CI = 1.04–1.05) ( Yan et al, 2022 ). Another large cohort study in Canada involving 1,807,133 individuals revealed that an IQR increase in time-varying exposure to PM2.5 (IQR = 3.90 μg/m 3 ) was associated with an HR of 1.016 (95% CI = 1.003–1.028; Smargiassi et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…DPM is aff ected by fuel source, engine type, and operating conditions. Owing to its small particle size, DPM remains in the atmosphere for a long duration, adsorbing harmful substances such as various trace metals, Polycyclic Aromatic Hydrocarbons (PAHs), and nitroarenes, showing various chemical variabilities [10]. DPM enters cells, attaches to blood vessels, causes respiratory diseases, and move to other tissues through the blood, causing cardiovascular and lung function aggravation over long-term exposure, eventually leading to death [11].…”
Section: Introductionmentioning
confidence: 99%